Еволюція системи загальних принципів права Європейського Союзу - Юхимюк, О.; Iukhymiuk, О. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті проведено історико-правовий аналіз еволюції системи загальних принципів права Європейського Союзу як елемента складної правової системи Європейського Союзу, що сформувалася внаслідок узагальнення правових систем різних країн, що стали учасницями Європейського Співтовариства. Система загальних принципів права Європейського Союзу зазнала суттєвих змін в декількох напрямках: розширилося нормативне закріплення як загальних, так і спеціальних принципів права Європейського Союзу; формулюванню, закріпленню і наповненню змістом загальних принципів права безпосередньо сприяло функціонування Суду Європейського Союзу; Лісабонський договір 2007 р. сформував єдину і взаємозалежну комплексну систему принципів права, доповнивши її категорією«цінності Союзу». The article offers historical and legal analysis of the evolution of the system of the principles of European Union law as an element of a complex legal system of the European Union, which was formed in the result of generalization of the legal systems of various countries, which have become members of the European Community. The European Union law general principles system has experienced significant modifications in several directions: the normative consolidation of both general and specific principles of the European Union law has been expanded, including the Memorandum and the amendments thereto; the functioning of the European Union Court of Justice contributed greatly to the formulation, consolidation and improving the content of the general principles of law; the Treaty of Lisbon in 2007 identified the major essentialchanges and amendments, having established a unified complex and interdependent system of principles of law, having added to it the category «values of the Union». Each of the general principles of law requires separate independent scientific research, which would not only consider its historical and legal aspects and interrelation of it with adjacent categories, but would also contribute to the identification of gaps or conflicts in the application of this or that principle, predicting directions of its development.
Evolution of the European Union Law Common Principles System
Keywords: принципи права; принципи права Європейського Союзу; джерела права; principles of law; the principles of European Union law; sources of law